2022
DOI: 10.3389/fvets.2022.1049910
|View full text |Cite
|
Sign up to set email alerts
|

Thermal manipulation modifies embryonic growth, hepatic free amino acid concentrations, and hatching performance in layer-type chicks

Abstract: Thermal manipulation (TM) of incubation temperature has been demonstrated to alter metabolism and post-hatch thermotolerance in broiler strains (meat-type chickens). Fewer reports were focused on layer-type chickens and there was no report on amino acid metabolism during TM in layer-type embryos. In this study, we investigated the effects of TM on embryonic development, hepatic amino acid metabolism, and hatching performance in layer-type chickens. Fertilized eggs were incubated under control thermoneutral tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Incubation conditions have a substantial impact on embryonic development, hatchability, chick quality, and posthatch performance ( Han et al, 2022 ; Rocha et al, 2022 ; Fares et al, 2023 ; Al-Zghoul et al, 2023 ). Hatchability and chick quality are 2 crucial factors that determine the success of a hatchery ( Yassin et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Incubation conditions have a substantial impact on embryonic development, hatchability, chick quality, and posthatch performance ( Han et al, 2022 ; Rocha et al, 2022 ; Fares et al, 2023 ; Al-Zghoul et al, 2023 ). Hatchability and chick quality are 2 crucial factors that determine the success of a hatchery ( Yassin et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hatchability and chick quality are 2 crucial factors that determine the success of a hatchery ( Yassin et al, 2008 ). Several studies have been conducted to discover strategies to improve these factors, and one of the most effective methods is temperature manipulation ( Han et al, 2022 ; Rocha et al, 2022 ; Tona et al, 2022 ; Al-Zghoul et al, 2023 ). They demonstrated that by controlling the temperature during incubation, it is possible to boost the hatchability percentage and chick quality by improving the embryo's physiological and biological functions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations